Addressing vaccine hesitancy: The potential value of commercial and social marketing principles and practices. Issue 34 (14th August 2015) - Nowak, Glen J.; Gellin, Bruce G.; MacDonald, Noni E.; Butler, Robb; the SAGE Working Group on Vaccine Hesitancy, 2
Abstract Many countries and communities are dealing with groups and growing numbers of individuals who are delaying or refusing recommended vaccinations for themselves or their children. This has created a need for immunization programs to find approaches and strategies to address vaccine hesitancy. An important source of useful approaches and strategies is found in the frameworks, practices, and principles used by commercial and social marketers, many of which have been used by immunization programs. This review examines how social and commercial marketing principles and practices can be used to help address vaccine hesitancy. It provides an introduction to key marketing and social marketing concepts, identifies some of the major challenges to applying commercial and social marketing approaches to immunization programs, illustrates how immunization advocates and programs can use marketing and social marketing approaches to address vaccine hesitancy, and identifies some of the lessons that commercial and non-immunization sectors have learned that may have relevance for immunization. While the use of commercial and social marketing practices and principles does not guarantee success, the evidence, lessons learned, and applications to date indicate that they have considerable value in fostering vaccine acceptance.